Native New Zealand plants with inhibitory activity towards Mycobacterium tuberculosis - Swift Simon; Murikoli Rekha V; Altaf Mudassar; Earl Emma A; O'Toole Ronan (BMC, 2010)
Abstract Background Plants have long been investigated as a source of antibiotics and other bioactives for the treatment of human disease. New Zealand contains a diverse and unique flora, however, few of its endemic plants have been used to treat tuberculosis. One plant, Laurelia novae-zelandiae, was reportedly used by indigenous Maori for the treatment of tubercular lesions. Methods Laurelia novae-zelandiae and 44 other native plants were tested for direct anti-bacterial activity. Plants were extracted with different solvents and extracts screened for inhibition of the surrogate species, Mycobacterium smegmatis. Active plant samples were then tested for bacteriostatic activity towards M. tuberculosis and other clinically-important species. Results Extracts of six native plants were active against M. smegmatis. Many of these were also inhibitory towards M. tuberculosis including Laurelia novae-zelandiae (Pukatea). M. excelsa (Pohutukawa) was the only plant extract tested that was active against Staphylococcus aureus. Conclusions Our data provide support for the traditional use of Pukatea in treating tuberculosis. In addition, our analyses indicate that other native plant species possess antibiotic activity.